ANALISIS PENGENDALIAN KUALITAS PRODUK RV FRAME PADA PT X: ANALISIS PENGENDALIAN KUALITAS PRODUK RV FRAME PADA PT X - Nugroho, Randy Yudho; Azharman, Zefri (Computer Science and Industrial Engineering, 2019)
The research inted to analyze whether the implementation of a quality control system in this company has been controlled based on determined quality targets or not. As well as looking for factors that cause product defects in the production process of RV frames in PT X. This research uses statistical process control method. The results showed that the quality control of the Rv frame production process at PT X had not been controlled as evidenced in the control chart with 6 out of 51 data outside the control limit and in the Pareto diagram table, the percentage of defects was flahes/extra material 32.25%. , product defects due to short mold amounting to 29.64% and product defects due to discoloration of 27.67% then product defects due to overcut 8.92% and product defects due to bending at 1.45% and because it was broken by 0.08%. The factors that cause this damage are machine, human, material, and method factors, but of these four factors there are two factors that cause the most dominant damage affecting quality, namely machine factors and human factors.